Comparative Efficacy of Ribosome-Inactivating Protein-Containing Immunotoxins in 2D and 3D Models of Sarcoma - Giulia Calafato; Massimo Bortolotti; Letizia Polito; Andrea Bolognesi (Toxins)
Sarcomas are very complex and clinically challenging mesenchymal tumors. Although the standard therapeutic approach has improved the 5-year survival rate, many patients experience local relapses and/or distant metastases. To improve patient outcome, new strategies need to be investigated. Immunotoxins (ITs) based on rRNA N-glycosylases (also named ribosome-inactivating proteins, RIPs) are promising tools for cancer therapy because, by combining rRNA-glycosylase’s high cytotoxicity with carrier selectivity, they can specifically eliminate target neoplastic cells. In the last few years, 3D models have been extensively used in cancer research, particularly for target-specific drug screening. This study aimed to evaluate the possibility of utilizing ribosome-inactivating protein (RIP)-containing ITs to selectively target TfR1-, EGFR1- and Her2-expressing sarcoma adherent cells (ACs), spheroids (SSs) and organoids (ORs). To compare Its’ efficacy and ability to induce apoptosis, we performed dose–response viability and caspase 3/7 activation assays on rhabdomyosarcoma and osteosarcoma ACs, SSs and ORs treated with Tf-IT, αEGFR1-IT and αHer2-IT. Our results indicate that, compared to the corresponding unconjugated RIPs, all ITs showed increased cytotoxicity in sarcoma ACs. Despite the increased complexity characterizing 3D models, the higher IC50 differences between ITs and unconjugated RIPs were obtained in ORs, which appeared more resistant to the nonspecific killing of the RIPs than either the ACs or SSs, thus augmenting the therapeutic window between unconjugated and conjugated RIPs. IT induced a more delayed apoptosis in 3D compared to 2D models. Our results provide essential outcomes for the potential use of these RIP-based ITs as a therapeutic strategy to treat sarcoma.